Mutant p53 Gain-of-Function: Role in Cancer Development, Progression, and Therapeutic Approaches - Alvarado-Ortiz, Eduardo; de la Cruz-López, Karen Griselda; Becerril-Rico, Jared; Sarabia-Sánchez, Miguel Angel; Ortiz-Sánchez, Elizabeth; García-Carrancá, Alejandro (Frontiers in Cell and Developmental Biology, 2021)
Frequent p53 mutations (mutp53) not only abolish tumor suppressor capacities but confer various gain-of-function (GOF) activities that impacts molecules and pathways now regarded as central for tumor development and progression. Although the complete impact of GOF is still far from being fully understood, the effects on proliferation, migration, metabolic reprogramming, and immune evasion, among others, certainly constitute major driving forces for human tumors harboring them. In this review we discuss major molecular mechanisms driven by mutp53 GOF. We present novel mechanistic insights on their effects over key functional molecules and processes involved in cancer. We analyze new mechanistic insights impacting processes such as immune system evasion, metabolic reprogramming, and stemness. In particular, the increased lipogenic activity through the mevalonate pathway (MVA) and the alteration of metabolic homeostasis due to interactions between mutp53 and AMP-activated protein kinase (AMPK) and Sterol regulatory element-binding protein 1 (SREBP1) that impact anabolic pathways and favor metabolic reprograming. We address, in detail, the impact of mutp53 over metabolic reprogramming and the Warburg effect observed in cancer cells as a consequence, not only of loss-of-function of p53, but rather as an effect of GOF that is crucial for the imbalance between glycolysis and oxidative phosphorylation. Additionally, transcriptional activation of new targets, resulting from interaction of mutp53 with NF-kB, HIF-1α, or SREBP1, are presented and discussed. Finally, we discuss perspectives for targeting molecules and pathways involved in chemo-resistance of tumor cells resulting from mutp53 GOF. We discuss and stress the fact that the status of p53 currently constitutes one of the most relevant criteria to understand the role of autophagy as a survival mechanism in cancer, and propose new therapeutic approaches that could promote the reduction of GOF effects exercised by mutp53 in cancer.